Finite element modeling for structural dynamic analysis of bolted joints under uncertainty. (2017) - Langer, P.; Sepahvand, K.; Guist, C.; Marburg, S.
Abstract: Bolted joint components have a major impact on the dynamic behavior of structural systems. They exhibit various uncertainties associated with joint materials, contact conditions, geometric parameters, clamping forces, the chosen pressure distribution, etc. Consequently, predicting the structural dynamic behavior of such components employing numerical models such as finite element (FE) method is an extremely challenging issue. This paper focuses on the critical points concerning the FE modeling for structural dynamic analysis of bolted connections to achieving reasonably accurate simulation results. In this regard, sample components of an automotive engine transmission system with bolted joints are investigated. Experimental modal analysis via laser Doppler vibrometry is used to estimate the natural frequencies of the components under uncertainty in pressure distribution, excitation amplitude and clamping lengths. The FE model is then updated to achieve a reasonable accuracy in dynamic responses compared to experimental results.